2009
DOI: 10.1590/s1413-86702009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of peginterferon alfa-2B combined with ribavirin for the treatment of chronic hepatitis C in Brazil

Abstract: The treatment of chronic hepatitis C (CHC) with peginterferon alpha-2b/ribavirin (PegIFN + Rib) produced larger sustained viral response (SVR) compared to the conventional (non-pegylated) interferon/ribavirin (IFN + Rib), but its cost-effectiveness was not assessed in Brazil. We developed a Markov model to mirror the natural disease history and cohorts of patients with hepatitis C virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
8
0
3
Order By: Relevance
“…34 Specifically, costs per quality adjusted life year (QALY) when compared with no treatment are generally estimated to fall below cost effectiveness thresholds (e.g., < £30,000 per QALY or < U.S.$50,000 per QALY), although one study found that antiviral treatment may not be cost-effective in patients with genotype 1 who have progressed to cirrhosis. [34][35][36][37] In the present study, HCV-related antiviral therapy costs (e.g., interferon α-2a and α-2b, interferon alphacon a, pegylated interferon α-2a and α-2b, and ribavirin), represented a large component of drug costs for HCV patients without AdvLD or with compensated cirrhosis, with PPPY costs for antiviral therapy of $2,445 and $3,243, respectively. HCV antiviral PPPY costs for HCC and transplant patients were less at $1,599 and $1,653, respectively, which represents a smaller proportion of both overall drug costs and incremental drug costs between HCC and transplant patients and their matched comparison enrollees.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…34 Specifically, costs per quality adjusted life year (QALY) when compared with no treatment are generally estimated to fall below cost effectiveness thresholds (e.g., < £30,000 per QALY or < U.S.$50,000 per QALY), although one study found that antiviral treatment may not be cost-effective in patients with genotype 1 who have progressed to cirrhosis. [34][35][36][37] In the present study, HCV-related antiviral therapy costs (e.g., interferon α-2a and α-2b, interferon alphacon a, pegylated interferon α-2a and α-2b, and ribavirin), represented a large component of drug costs for HCV patients without AdvLD or with compensated cirrhosis, with PPPY costs for antiviral therapy of $2,445 and $3,243, respectively. HCV antiviral PPPY costs for HCC and transplant patients were less at $1,599 and $1,653, respectively, which represents a smaller proportion of both overall drug costs and incremental drug costs between HCC and transplant patients and their matched comparison enrollees.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Fonseca et al 61 developed a Markov model to mirror the natural disease history in cohorts of patients with hepatitis C virus who received peginterferon alpha-2b with ribavirin or interferon alpha-2b and ribavirin treatment for 48 or 24 weeks, according to their viral genotype and liver histology; they concluded that peginterferon alpha-2b with ribavirin is a cost-effective therapy for treating naïve chronic hepatitis C adult patients compared to the interferon alpha-2b and ribavirin regime, regardless of the viral genotype. Santos et al 62 described fulminant hepatic failure in eight adults and children from a public hospital in Rio de Janeiro, Brazil caused by hepatitis B and one case of severe acute hepatitis caused by hepatitis A. Veras et al 63 described the prevalence of chronic hepatitis C virus in the state of Piaui in northeastern Brazil; Zahdi et al 64 examined the costs and benefits of preventing the disease by utilizing the vaccine for hepatitis A in the southern Brazilian state of Parana.…”
Section: Methodsmentioning
confidence: 99%
“…Estudos avaliaram, no cenário brasileiro, a relação do custo/efetividade das tecnologias disponíveis para o tratamento da hepatite C em indivíduos monoinfectados 14,15,16,17 . Ainda assim, há uma lacuna significativa do custo/efetividade do tratamento de indivíduos coinfectados VHC/ HIV, principalmente à luz das mais atuais diretrizes para o tratamento da coinfecção no âmbito do Sistema Único de Saúde (SUS) 12 .…”
Section: Introductionunclassified